Topografie der Einbildungskraft (Re-)Lektüren aus dem Diskurs des Gedenkens - Kock, Sabine (2022)
Starting from Adorno's dictum, what arts and culture could be after the reality of Auschwitz, the philosopher Sabine Kock takes central argumentations of Theodor W. Adorno and Max Horkheimer, Hannah Arendt, Jean-François Lyotard, Sarah Kofman, Georges Didi-Huberman into view. For all of them imagination is an indispensable philosophical category and social force, but in fundamentally different ways. Kant proves to be a central reference: on the one hand as the guarantor of an irretrievably past, coherent world, on the other hand as the source of a fateful turn in the dialectic of enlightenment. Film material of the trial against Adolf Eichmann as well as an epilogue referring to the reflective narrator Ruth Klüger add this perspective.